Prosthetic Rehabilitation of a Patient with an Ocular Defect: A Simplified Approach - Shivakumar Puranik; Anoop Jain; Sunil Ronad; Sachhi Ramesh; Jagadeesh MS; Puttaraj Kattimani (Case Reports in Ophthalmological Medicine)
Mutilation of a portion of a face can cause a heavy impact on the self-image and personality of an individual. Acceptable cosmetic results usually can be obtained with a facial prosthesis. This paper describes prosthetic rehabilitation of a 60-year-old male patient having a left ocular defect. A technique to fabricate heat polymerizing polymethyl methacrylate was illustrated. The resultant prosthesis was structurally durable and aesthetically acceptable with satisfactory retention. The importance of meticulous treatment planning to tackle the challenges faced in fabricating an ocular prosthesis is explained with the relevant literature.